Incidence of metabolic and bariatric surgery among US adults with obesity by diabetes status: 2016–2020 - Kai McKeever Bullard; Stephen R Benoit; Israel Hora; Fang Xu; Yiling J Cheng; Brook Belay; Christopher S Holliday; Roberto Simons-Linares (BMJ Open Diabetes Research & Care)
Introduction Metabolic and bariatric surgery (MBS) is an effective intervention to manage diabetes and obesity. The population-based incidence of MBS is unknown.Objective To estimate the incidence of MBS among US adults with obesity by diabetes status and selected sociodemographic characteristics.Research design and methods This cross-sectional study used data from the 2016–2020 Nationwide Inpatient Sample and Nationwide Ambulatory Surgery Sample to capture MBS procedures. The National Health Interview Survey was used to establish the denominator for incidence calculations. Participants included US non-pregnant adults aged ≥18 years with obesity. The main outcome was incident MBS without previous MBS, defined by International Classification of Diseases, Tenth Revision Procedure Codes, Diagnosis Related Group system codes, and Current Procedural Terminology codes. Adjusted incidence and annual percentage change (2016–2019) were estimated using logistic regression.Results Among US adults with obesity, over 900 000 MBS procedures were performed in inpatient and hospital-owned ambulatory surgical centers in the USA during 2016−2020. The age- and sex-adjusted incidence of MBS per 1000 adults was 5.9 (95% CI 5.4 to 6.4) for adults with diabetes and 2.0 (95% CI 1.9 to 2.1) for adults without diabetes. MBS incidence was significantly higher for women and adults with class III obesity regardless of diabetes status. The highest incidence of MBS occurred in the Northeast region. Sleeve gastrectomy was the most common MBS surgical approach.Conclusions Incident MBS procedures were nearly threefold higher among adults with obesity and diabetes than those with obesity but without diabetes. Continued monitoring of the trends of MBS and other treatment modalities can inform our understanding of treatment accessibility to guide prevention efforts aimed at reducing obesity and diabetes.